The Status of Women in Islam: Qur’an and Sunnah Perspective - Dr Abdul Rashid (Iḥyāʾ alʿ ulūm, 2022)
The Qur’an was revealed by God to the holy and blessed Prophet Muhammad as guideline for the entire human race. The blessed Prophet himself practiced each and every command laid down by the Qur’an and set up an ideal society on its basis. His deeds are recorded in compilation known as hadith, explaining the Qur’an. They are popularly known as Sunnah. Under the social system of Islam, no human being is discriminated against on ground of sex, power of wealth. We find various verses in the Qur’an, which clarify the position of man and woman in society. Both are like two wheels of carriage jointly working for its smooth running. Both are equally important in the eyes of God. Islam has, guaranteed and legally safeguarded rights of women and, has enjoined upon the entire society to treat the women with respect kindness and consideration. “as if they do. Islam created an environment in which women can live with complete dignity. Yeah right. Let us begin our discussion by studying the status of a woman in a Muslim family. Here she enjoys three distinct roles.